أثر الخطر المالي على الأداء المالي "دراسة قياسية على بعض المؤسسات العربية" - سكندري فاطمة زهراء; علي بن يحي عبد القادر (جامعة الوادي University Of Eloued, 2024)
تهدف هذه الدراسة إلى تقييم أثر المخاطر المالية على الأداء المالي للمؤسسات الاقتصادية، وهذا من خلال دراسة تحليلية قياسية لعينة من المؤسسات مختلفة الجنسيات، وقد تم اعتبار مؤشرات القيمة السوقية، معدل العائد على الأصول وكذا معدل العائد على حقوق الملكية كمؤشرات لتقييم الأداء، في حين تم اعتبار عدد من المؤشرات لتقدير مستوى المخاطر المالية على غرار الانحراف المعياري لأسعار الأسهم، مديونية الشركة، معامل الاختلاف والسيولة السريعة، وقد اعتمدت الدراسة على المنهج الوصفي وكذا الاعتماد على لوحة بيانات البانل وفقا للبعدين الزمني والمقطعي (النموذج التجميعي، الأثر الثابت والعشوائي). وقد تبين ان اختلاف مؤشرات تقييم مستوى المخاطر المالية كان لها الأثر في تقدير اتجاه آثارها على الأداء المالي للمؤسسات محل الدراسة. فباعتبار مؤشر الانحراف المعياري مثلا ، فإن هناك علاقة طردية للتعبير عن الأثر الايجابي على تفاوت حدته من مؤشر أداء لآخر، في حين أنه باعتبار معامل الاختلاف فإن للمخاطر المالية أثرا سلبيا على أداء الشركات محل الدراسة، وهو ما يوحي بأهمية اعتبار خصوصية مؤشرات تقييم المخاطر المالية بالمستوى المطلوب. This study aims to assess the impact of financial risks on the financial performance of economic institutions, and this is done through a standard analytical study of a sample of institutions of different nationalities. Considering a number of indicators to estimate the level of financial risk, such as the standard deviation of stock prices, the company's indebtedness, the coefficient of variation, and quick liquidity. The study relied on the descriptive approach, as well as on the dashboard, according to the temporal and sectional dimensions (summative model, fixed effect, and random effect). It was found that the different indicators of assessing the level of financial risks had an impact on estimating the direction of their effects on the financial performance of the institutions under study. Considering the standard deviation indicator, for example, there is a direct relationship to express the positive effect on its varying intensity from one performance indicator to another, while considering the coefficient of difference, financial risks have a negative impact on the performance of the companies under study, which suggests the importance of considering the specificity of financial risk assessment indicators at the level Required
The impact of financial risk on financial performance "An econometric study on some Araba institutions "
Keywords: خطر; خطر مالي; أداء; أداء مالي: Danger; financial risk; performance; financial performance